Web-Based Pharmacy Cashier Application Development Design - Marisma, Murni; Wibowo, Feri; Purwanto, Lahan Adi; Fauzan, Achmad (Journal of Intelligent Systems and Information Technology, 2024)
The cashier system at Arca Mandiri Pharmacy still uses manual transaction recording services; namely, the cashier uses recording transaction calculations in the sales transaction logbook and manually records drug stock in the drug stock book. This results in less effective and efficient recording of transactions and the stock of medicinal goods. Facilities and services to cashiers are expected to be provided more effectively and efficiently using a web-based cashier application so that it will improve service in transactions for customers. The system development method used is a waterfall model approach with four stages, namely analysis, design, code, and testing. The web-based cashier application implementation model allows the system to be used by cashiers and administrators with its advantages, namely automatically calculating the total amount of drug order prices in sales transactions, stock calculations, and routine transaction reports. The Cashier Application implemented at the website-based Arca Mandiri Pharmacy helps facilitate sales transactions, processing drug stock data, and printing reports that can be done quickly so that it is more efficient and effective in service.